CO preferential oxidation with Cu/CeO2-Al2O3 and CuPt/CeO2-Al2O3 catalysts - Núñez, Natalia Elena (2014)
This paper focuses on the preparation, characterization and analysis of the catalytic activity of a series of alumina-supported Cu and Pt catalysts modified with different amounts of cerium, in order to employ them in the carbon monoxide preferential oxidation (CO-PROX) reaction. The catalysts containing only copper as metallic phase allowed us to obtain very good conversion of CO to CO2, reaching a maximum of 70% conversion for the catalyst with higher concentration of Cu supported on the alumina modified with the highest concentration of Ce (0.54 wt% Cu, 25 wt% Ce). For catalysts containing both Cu and Pt the conversions achieved were reasonably good, although lower than for the monometallic catalysts, but at lower temperature. All the catalysts were characterized by different physicochemical techniques: temperature-programmed reduction, X-ray diffraction, UV-VIS diffuse reflectance spectroscopy and surface area. The presence of ceria in these catalysts is pointed as one of the main reasons for their good activity, mainly because the CeO2 increases the availability of O2 to be used in this oxidation reaction